Expert System To Identify Insomnia Problems In Adults Using Forward Chaining Method - Ayu Dwi Ratna Ningsih; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
Insomnia is a symptom that is often experienced by adults of productive age, such as having difficulty starting to sleep, often waking up at night. With the development of technology, most of the jobs have involved technology. Expert systems are artificial intelligence that is growing rapidly in the world of technology. With an expert system, a person can be helped according to their needs when it is difficult to meet directly with the expert. The purpose of this study was to make it easier for researchers to identify insomnia problems based on the symptoms experienced by the adults around them. The research method used is the forward chaining method. while the data collection technique is quantitative data technique. The desired result of this study is the reduction of a person affected by insomnia problems and the Expert System can provide solutions to reduce Insomnia Problems such as relaxation music before consulting a doctor.